A report on the practice in industry training in fish culture - Flores, Sepas L. (College of Fisheries, University of the Philippines, 1950)
Rice and fish is our staple food and, although the Philippines is topographically favored for the abundant, acquisition of these prime commodities, yet we have not attained that stage of sufficiency. Fishpond industry is one of the most dependable and sure ways of supplying our people with fish. Presently there are about 70,000 hectares of bangos fishpond scattered throughout the country. This annually produces approximately24, 500,000 kilograms of fish valued at about P40,,000,000.00. even in adverse weather conditions this industry can steadily supply iour market with fish. Because of the great profit derived, those who know this business fairly well are still exerting every effort to expand their fishpond. The calculated area does not mean, however, that the Philippines is already short of fishpond flats of approximately 430,000 hectares. This is not a potential wealth of the Philippines lying idle and waiting for capitalists. If scientifcallycultivated, this seemingly useless portion of our land will eventually and steadily increase the wealth of the investors. Subsequently, it will help solve the present unemployment problem, help supply the population of their protein and last but not least, increase the income of our government. The attention of our rich men is therefore called fishing industry (fish culture) because of the above mentioned possibilities.